Collaborative, patient-centred care model that provides tech-enabled treatment of opioid use disorder via telehealth - Rollston, Rebekah; Gallogly, Winifred; Hoffman, Liza; Tewari, Eshan; Powers, Sarah; Clear, Brian (BMJ innovations, 2022)
‘Higher’ levels of OUD care offer additional structured support and in turn require additional commitment from patients: opioid treatment programmes require everyday attendance for at least a 90-day initial period; intensive outpatient programmes require at least 9 hours of structured programming each week per criteria set by the American Society of Addiction Medicine; partial hospitalisation programmes require at least 20 hours of structured programming each week; and residential and inpatient programmes offer continuous support.5 In-person treatment settings may offer alternative medications to buprenorphine, including methadone and naltrexone, which, for various reasons, are not feasible to offer via telehealth. In addition to advancing patient-centred care, research has shown that tech-enabled care can support clinical decision-making.19 No Institutional Review Board approval was required for this Early-Stage Innovation Report because developing the report did not involve interaction or intervention with human subjects or access to individually identifiable patient information; all data were collected in the course of routine clinical care and reviewed in aggregate. Telehealth visits are encrypted using the Advanced Encryption Standard.21 Patients have access to tech and clinical support staff on various ‘chat channels’ within the Bicycle Health app.20 Clinical support staff can review provider notes and reinforce instructions to patients; direct patients to information about treatment expectations; (re)schedule appointments routinely or urgently; call pharmacies to provide support for prior authorisations; and share mental health and self-management resources. Recent research demonstrates that nearly 30% of US pharmacies report limitations to filling buprenorphine prescriptions, and 20% of US pharmacies would not fill buprenorphine prescriptions entirely.23 To address these access issues, Bicycle Health built a pharmacy finder tool (on top of a dataset of all pharmacies in the USA) that allows clinical support staff to identify the pharmacy ahead of a patient’s first visit that is geographically nearest to the patient, most likely to have buprenorphine in stock based on history, accepts the patient’s insurance, and does not have a reported history of stigmatising or declining service to patients receiving tele-OUD treatment.